29 Development of a novel weight-based steroid emergency plan for patients with Duchenne Muscular Dystrophy. (15th December 2021) - Tollerfield, Sally; Atterbury, Abigail; Wadey (nee Antell), Hannah; Craig, Sian; Smith, Natalie; Sarkozy, Anna; Manzur, Adnan; Dattani, Mehul; Hoskins, Steve; Katugampola, Harshini
Abstract : Background: Long-term glucocorticoid therapy with Prednisolone or Deflazacort has improved outcomes in patients with Duchenne Muscular Dystrophy (DMD), however recommended dosages suppress the hypothalamic-pituitary-adrenal axis, leading to adrenal insufficiency. All boys prescribed glucocorticoid therapy should be assumed to have adrenal suppression, and therefore at risk of adrenal crisis during illness or stress. The updated DMD Care Considerations consensus document (2018) recommends implementation of emergency plans. However, no unified national or international guidance for illness management for this cohort exists. Previously emergency sick day plans were not consistently in place and on national survey of 6 other Trusts, it was clear that advice and education for sick day steroid regimens was variable. Aim: We sought to develop a weight-based steroid emergency regimen for DMD patients, many of whom are non-ambulant, and in whom accurate measurements for body surface area can be challenging. Methods: A novel weight-based regimen of stress doses of oral hydrocortisone given 6 hourly was devised. This is to be implemented when needed, in addition to the glucocorticoid regimen the patient was taking for disease. Results: Approval from the Drugs and Therapeutics committee was obtained for a novel weight-based stress dose regimen of hydrocortisone. Training and education were provided to increase awareness of adrenal insufficiency among patients and families. Families are educated about stress dosing plans, recognising signs/symptoms of adrenal crisis, and trained to give IM Hydrocortisone injections and provided with written information. Adrenal 'Flags' have been added to our electronic patient records alerting staff that these patients are at risk of adrenal crisis. Conclusion: Anecdotally families report faster recovery times from illness since using stress-doses of hydrocortisone alongside their usual glucocorticoid. The development of a unified, consistent approach to illness management, alongside structured education for DMD patients and families, are initial actions towards improving clinical outcomes.